Implementation Of A Web-Based Health Equipment Store System Using React And Node.JS - Paramesti, Risma; Shafira, Reihan Rachma (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
The rapid development of information technology has encouraged the utilization of web-based systems to improve data management efficiency and transaction processes across various sectors, including the healthcare sector. Manual management of medical equipment stores often leads to several problems, such as transaction delays, difficulties in managing product and inventory data, and limited access to information for customers. These conditions indicate the need for an information system that can support business processes more effectively and in a structured manner. This study aims to implement a web-based medical equipment store system that facilitates product management, sales transactions, and interactions between administrators and customers efficiently. The system development method used in this study is the Waterfall method, which consists of literature study, requirements analysis, system design, implementation, testing, and conclusion stages. The system is developed using a separated front-end and back-end architecture, where React is utilized to build an interactive and responsive user interface, Node.js is employed as the back-end to manage application logic and API services, and MySQL is used as the database management system. The results show that the developed system is able to meet both functional and non-functional requirements and effectively supports online product management and sales transactions. Based on the results of black box testing, all main system features function according to the specified requirements. Therefore, the proposed web-based medical equipment store system is expected to serve as an alternative solution to enhance efficiency in managing and delivering services for medical equipment stores.